Reducing Time to Discharge after Chemotherapy by Standardizing Workflow and Providing Outpatient Intravenous Hydration. Issue 4 (July 2021) - Sitthi-Amorn, Jitsuda; Ast, Allison; Harper, Erin; Abbott, Brian; Alsaek, Yaser; Bourland, Wendy; Courtney, Rachael; Madni, Arshia; Sharma, Aditya; Spencer, Christopher; McCurrach, Lane; Morgan, Stacey; et al.
Abstract : Introduction: Patients receiving cyclophosphamide or ifosfamide chemotherapy require intravenous fluid hydration to prevent hemorrhagic cystitis. In selected patients without medical contraindications (ie, excess nausea/vomiting), this hydration may be completed after discharge. We aimed to reduce the time to discharge after completing mesna in patients receiving cyclophosphamide or ifosfamide therapy on an inpatient chemotherapy service. Methods: The quality improvement team performed a medical record review to capture the time to discharge after mesna therapy and the readmission rate and used quality improvement methods to redesign discharge workflow and increase patient involvement with the discharge process. Results: From August 2017 through July 2018, there were 160 admission encounters (73 patients) for cyclophosphamide or ifosfamide on a dedicated chemotherapy service. Of those encounters, 89 (55.6%) were appropriate for outpatient hydration; 48 (53.9%) of these encounters involved a patient who elected to receive outpatient hydration. Although the median time to discharge for the whole cohort did not change, in encounters where patients chose intravenous outpatient hydration, the median time to discharge was reduced from 2.82 to 0.66 hours (76.6% reduction) after implementing the new discharge workflow. No patients experienced readmission within 48 hours. Conclusions: Discharge workflow redesign and standardization reduced the time to discharge after chemotherapy in patients who chose outpatient hydration. Outpatient intravenous hydration after cyclophosphamide or ifosfamide appears safe and feasible in selected patient populations. Abstract : Supplemental Digital Content is available in the text.